1976
DOI: 10.1111/j.1476-5381.1976.tb10401.x
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Micro‐electrophoretically Applied 1‐3,4‐dihydroxyphenylalanine (Dopa) on Single Cortical Neurones

Abstract: 1 The technique of microelectrophoresis was used in order to compare the actions of L-3,4-dihydroxyphenylalanine (DOPA) and noradrenaline on single neurones in the cerebral cortices of cats and rats. 2 DOPA could both excite and depress cortical neurones. Cells excited by DOPA were also excited by noradrenaline and cells depressed by DOPA were also depressed by noradrenaline. 3 In the case of both excitatory and depressant responses, DOPA appeared to be less potent than noradrenaline. 4 Responses to DOPA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

1977
1977
1979
1979

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
2
2
1
Order By: Relevance
“…The results with the adrenoceptor antagonists support our suggestion, based on the action of the agonists, that excitatory responses are mediated by a-, and depressant responses are mediated by /3-receptors. In agreement with previous findings (Johnson et al, 1969;Bevan et al, 1974a;Bevan et al, 1976a), we have found that the a-adrenoceptor blocking agents could reversibly antagonize excitatory responses to adrenoceptor agonists, while excitatory responses to ACh were not affected. On the other hand, depressant responses to adrenoceptor agonists seemed to be resistant to a-adrenoceptor blocking agents (see Figure 4).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The results with the adrenoceptor antagonists support our suggestion, based on the action of the agonists, that excitatory responses are mediated by a-, and depressant responses are mediated by /3-receptors. In agreement with previous findings (Johnson et al, 1969;Bevan et al, 1974a;Bevan et al, 1976a), we have found that the a-adrenoceptor blocking agents could reversibly antagonize excitatory responses to adrenoceptor agonists, while excitatory responses to ACh were not affected. On the other hand, depressant responses to adrenoceptor agonists seemed to be resistant to a-adrenoceptor blocking agents (see Figure 4).…”
Section: Discussionsupporting
confidence: 93%
“…The /-receptor blocking agents, however, were also capable of antagonizing excitatory responses. This finding is in agreement with previous reports (Johnson et al, 1969;Bevan et al, 1974a;Bevan et al, 1976a). This observation might seem to argue against our hypothesis that the excitatory responses are mediated by a-receptors.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations